Implementasi Fungsi Dan Kewenangan Brigade Mobile Kepolisian Daerah Nusa Tenggara Timur Dalam Mencegah Tindak Pidana Terorisme Di Wilayah Perbatasan Indonesia Dengan Timur Leste - Yagie Sagita (Universitas Bengkulu, 2020)
This article discusses the role of the East Nusa Tenggara Regional Police Mobile Brigade in Preventing Terrorism in the Border Area. The background of this research is the implementation of the functions and authority of the East Nusa Tenggara Police Mobile Brigade in preventing terrorism in the Indonesian border region with Timor-Leste and what are the obstacles of the NTT Regional Police Mobile Brigade in conducting terrorism prevention in the border region of the State of Indonesia and the State of Timor Leste. This research is an empirical study. Data collection used in this study was a library research, interviews and analyzed qualitatively. Based on the results of the study, the number of personnel at the moment the National Police who are on duty at the Brimob Sub Den 2 Atambua Atambua NTT Regional Police are 114 personnel, which is considered quite in accordance with the ratio of cross-border post guard. that patrols were mostly carried out in the form of routine satker patrols (70%). The rest is done together with the Timor Leste government and government agencies involved in border management (10%). Other tasks are in the form of adjustments, in accordance with field conditions that occur at that time. Regarding the threat of terrorism, all respondents (100%) thought that the threat of terrorism ever occurred at the Border, namely the threat in the form of terror, 40% the threat of recruiting terrorism networks was only 30% and the threat of bombing occurred 30%. The obstacles faced by the NTT Regional Police Mobile Brigade in securing border areas are inadequate Accessibility to Border, Inadequate Facilities and Infrastructure, Minimal number of security personnel, Border Area Conflict, Inter-ethnic, ethnic and religious conflict, Lack of Community education about Nationality.Keywords: Mobile Brigade; Terrorism; Border; AbstrakPenelitian ini Peran Brigade Mobile Kepolisian Daerah Nusa Tenggara Timur Dalam Mencegah Terorisme Di Wilayah Perbatasan. Latar belakang dari penelitian ini adalah implementasi fungsi dan kewenangan Brigade Mobile Kepolisian daerah Nusa Tenggara Timur dalam mencegah terorisme di wilayah perbatasan Indonesia dengan Timor leste dan apa saja kendala Brimob Polda NTT dalam melakukan pencegahan terorisme di wilayah perbatasan Negara Indonesia dengan Negara Timor Leste. Penelitian ini merupakan penelitian empiris. Pengumpulan data yang digunakan dalam penelitian ini adalah library research, interview serta dianalisis secara kualitatif. Berdasarkan hasil penelitian, jumlah personal Saat ini anggota Polri yang bertugas di Sat Brimob Sub Den 2 Pelopor Atambua Polda NTT berjumlah 114 personal, hal tersbut dirasa cukup sesuai dengan rasio penjagaan pos lintas perbatasan negara. Bahwa patroli banyak dilakukan dalam bentuk patroli rutin satker (70%). Selebihnya dilakukan bersama pemerintah Timor Leste dan instansi pemerintah yang terkait pengelola perbatasan (10%). Tugas lain sifatnya berbentuk penyesuaian, sesuai dengan kondisi lapangan yang terjadi saat itu. Terkait ancaman terorisme, semua responden (100 %) berpendapat bahwa ancaman terorisme pernah terjadi di Perbatasan yaitu ancaman berbentuk terror 40 % ancaman perekrutan jaringan terorisme hanya 30 % dan ancaman bom terjadi 30 %. Adapun Kendala yang dihadapi sat brimob Polda NTT dalam mengamankan daerah perbatasan yaitu Aksesibilitas ke Perbatasan , Sarana dan prasarana yang belum memadai, Jumlah personel keamanan yang minim, Konflik Wilayah Perbatasan, Konflik antar etnis, suku dan agama, Kurangnya pendidikan Masyarakat tentang Kebangsaan.Kata Kunci: Brigade Mobile; Terorisme; Perbatasan;